Venture Capital Coordination in Syndicates, Corporate Monitoring, and Firm Performance - Kang, Jun-Koo; Li, Yingxiang; Oh, Seungjoon (Journal of Financial Intermediation, 2022)
This paper examines how the coordination of venture capital (VC) investors in their syndicates, as measured by their geographic concentration, affects firm performance and ex ante contractual terms. Using the introduction of new airline routes between the locations of VC investors as a shock to their coordination costs, we find that firms with geographically concentrated VC investors are more likely to exit successfully than other firms. Geographically proximate VC investors are also more likely to form syndicates in follow-up rounds and to use less intensive staged financing and fewer convertible securities.